Microstructure transformation of Mo–3Nb single crystal used for space thermionic reactor during welding. (July 2021) - Ma, Yan; Li, Xinxin; Zhu, Huiping; Tong, Zhenfeng
Abstract: Mo–3Nb single crystal is an important material used for processing the emitter of space thermionic reactor. The present research focuses on the microstructures of precipitated phases in the Mo–3Nb matrix and the joint welded by the vacuum electron beam, to reveal the microstructural transformation during the welding process. Characterization of the precipitates was conducted by transmission electron microscopy (TEM) with energy dispersive spectrum (EDS). The results show that the precipitated phases in the Mo single crystal matrix and the welds were all NbC of a crystalline cubic with space group: Fm-3m (225). After the welding, the morphology of NbC changed significantly, from a polygonal shape with a diameter of 100–200 nm to a thin rod with a length of 10–50 nm. High-temperature solution-quenching treatment on single crystal rods is suggested to further improve performance. Highlights: Precipitated phases formed in the Mo–3Nb single crystals made by the float zone melting method are crystalline cubic NbC. The morphology of precipitated phases changes from a polygonal shape to a thin rod after the welding. High-temperature solution-quenching treatment on single crystal rods is suggested to further improve performance.